Uncertainty in soil gas permeability measurements - Feng, Lingxia; Hu, Junguo; Jiang, Junjie (Frontiers in Environmental Science, 2025)
IntroductionSoil gas permeability is critical to the study of soil pore structure, soil gas transport, and crop growth.MethodsIn this paper, a pressure decay method is proposed to calculate soil gas permeability based on the law of conservation of mass, which is measured and compared with the steady-state method in a variety of soils, including compacted soils and soils with different moisture contents. The applicability of the two methods and the effects of compaction and water content on soil gas permeability were explored.ResultsThe experimental results show that in low-permeability soils, there is a bias in the measured values of the steady-state method. In contrast, the results calculated based on the pressure decay method are more accurate. Increasing the water content of the soil or compacting the soil results in a 20%–88% or 63%–93% decrease in soil gas permeability, respectively, with the degree of decrease correlating with the viscosity of the medium.DiscussionThe findings show that calculating soil gas permeability based on the pressure decay method helps compensate for the inaccuracy of the steady-state method in measuring results in low-permeability soils. This leads to a better evaluation of soil aeration conditions, which, in turn, serves environmental, agricultural, and ecological research.